The Effect of Company Size and Leverage on Company Value with Profitability as a Mediating Variable: A Systematic Literature Review - Ernitasari, Reny; Rahayu, Sri; Putra, Wirmie Eka (Transpublika Publisher, 2025)
Against a backdrop of heightened post-pandemic corporate debt levels and rising financial risks, understanding the determinants of corporate value is critical. This study aims to conduct a systematic review of the influence of company size and leverage on company value with profitability as an intermediary variable. Using a Systematic Literature Review (SLR) approach, this study analyzes 20 selected articles published in leading national journals to identify patterns, inconsistencies, and research gaps related to the determinants of company value. The review results show that the effect of company size on company value is significant; several studies report a positive effect because larger companies have greater resource capacity and market credibility. Leverage shows both positive and negative results, with some studies showing a positive impact through tax benefits, while the majority highlight negative effects due to increased financial risk and potential difficulties. Furthermore, profitability shows a varied role as an intermediary variable. In some cases, profitability successfully mediates the relationship between company size and leverage on company value, but in many studies, the mediating effect is insignificant due to low efficiency, high debt burden, or weak operational performance. Overall, this systematic review reveals that company value is shaped by multidimensional factors, emphasizing the importance of effective asset management, balanced capital structure, and strong profitability in enhancing company value.